Pengaruh Penggunaan Aplikasi Dana Dalam Transaksi Di Era Digitalisasi - Lisnawati Lisnawati (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2024)
Digital transactions are currently growing very rapidly. One of the most widely used digital transactions is the DANA digital wallet application. The use of the DANA application is widely used by people ranging from teenagers to adults. The DANA application makes it easy for its users to make financial transactions. This study aims to determine the effects of using the DANA application on transactions in the digital era. The research method used in this study is a qualitative method. Based on research that has been conducted by researchers, it is concluded that the use of the DANA application has a positive effect on transactions in the digital era. The use of the DANA application makes it easy for its users to make financial transactions. People can send money, receive money, withdraw money, pay for electricity tokens, buy credit and many others. The DANA application also offers various conveniences in making investments, for example gold investments.